Epitaxial growth of single-crystalline AlN layer on Si(111) by DC magnetron sputtering at room temperature. (2nd May 2018) - Shin, In-Su; Kim, Jongmyeong; Lee, Donghyun; Kim, Donghyun; Park, Yongjo; Yoon, Euijoon
Abstract: The epitaxial growth of an AlN layer on a Si(111) substrate at room temperature by DC magnetron sputtering was investigated. The predeposition of a 5-nm-thick Al layer on the Si substrate before the AlN deposition was found to be crucial for the epitaxial growth of the AlN layer. The orientation relationships of AlN/Al/Si were observed to be AlN ∥ Al ∥ Si and AlN ∥ Al[011] ∥ Si, indicating the epitaxial growth of the AlN layer on the Si(111) substrate. This epitaxial growth of the AlN layer was attributed to the smaller lattice mismatches between AlN and Al and AlN and Al[011] than that between AlN and Si .